ON EXISTENCE OF SOLUTION OF IMPLICIT VECTOR EQUILIBRIUM PROBLEMS FOR TRIFUNCTION - RAM, T.; KHANNA, A. K. (Journal of Nonlinear Analysis and Optimization: Theory & Applications (JNAO), 2024)
In this work, we introduce and study an extended version of implicit vector equilibrium problems for trifunction in real Hausdorff topological vector spaces. We prove some new existence results for the solution of these problems by using KKM lemma in real Hausdorff topological vector spaces. Some special cases are also discussed.